Anti-cancer Potential of Polysaccharide Extracted From Polygonatum sibiricum on HepG2 Cells via Cell Cycle Arrest and Apoptosis - Li, Mo; Liu, Yumeng; Zhang, Henan; Liu, Yanfeng; Wang, Weiming; You, Shengbo; Hu, Xinyu; Song, Meijun; Wu, Rina; Wu, Junrui (Frontiers in Nutrition, 2022)
Polygonatum sibiricum is one of the most widely used traditional Chinese medicine in China. Polygonatum sibiricum polysaccharide (PSP) is the main functional component of Polygonatum sibiricum. In this study, a water-soluble polysaccharide (PSP-1) was first isolated from Polygonatum sibiricum with a molecular weight of 38.65 kDa. Structural analysis was performed via methylation and FT-IR spectroscopy analyses, which in combination with NMR spectroscopy, revealed that PSP-1 has a → 4-α-D-Glcp-1 → backbone with the substitution at O-6 with the β-D-Glcp-1 → residues. Furthermore, PSP-1 exhibited potent and concentration-dependent anticancer effects, inducing HepG2 cell apoptosis and arresting the cell cycle at the G1 phase. Moreover, PSP-1 also decreased the mitochondrial membrane potential, damaged the nucleus of HepG2 cells, and increased the activity of caspase-9 and−3 in the intrinsic apoptotic pathways to induce HepG2 cell apoptosis. To conclude, PSP-1 might be a good candidate for the treatment of liver cancer, and this work provides important information for understanding the relationship between structure and antitumor activity of PSP-1, which is relevant for the treatment of hepatocellular carcinoma in clinic.